2006
DOI: 10.1002/cyto.a.20272
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed flow cytometric analyses of pro‐ and anti‐inflammatory cytokines in the culture media of oxysterol‐treated human monocytic cells and in the sera of atherosclerotic patients

Abstract: Background: Some oxysterols are identified in atheromatous plaques and in plasma of atherosclerotic patients. We asked whether they might modulate cytokine secretion on human monocytic cells. In healthy and atherosclerotic subjects, we also investigated the relationships between circulating levels of C‐reactive protein (CRP), conventional markers of hyperlipidemia, some oxysterols (7β‐hydroxycholesterol, 7‐ketocholesterol, and 25‐hydroxycholesterol), and various cytokines. Methods: Different flow cytometric be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
98
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 74 publications
6
98
1
1
Order By: Relevance
“…MCP-1 has a crucial role in intestinal chronic inflammation characterized by a macrophage infiltration; its protein expression was augmented in the mucosa of patients with IBD [34]. Contradictory results come from other studies on human monocytic U937 and THP-1 that reported the high capability of 20 mM 7b-OH to induce IL-8 secretion, but not MCP-1 [35,36]. These data agree with our previous results on differentiated CaCo-2 cells that reported a significant up-regulation of both expression and synthesis of IL-8 by 7b-OH; however undifferentiated intestinal cells behave differently.…”
Section: Discussionmentioning
confidence: 99%
“…MCP-1 has a crucial role in intestinal chronic inflammation characterized by a macrophage infiltration; its protein expression was augmented in the mucosa of patients with IBD [34]. Contradictory results come from other studies on human monocytic U937 and THP-1 that reported the high capability of 20 mM 7b-OH to induce IL-8 secretion, but not MCP-1 [35,36]. These data agree with our previous results on differentiated CaCo-2 cells that reported a significant up-regulation of both expression and synthesis of IL-8 by 7b-OH; however undifferentiated intestinal cells behave differently.…”
Section: Discussionmentioning
confidence: 99%
“…In U937 and THP-1 cells, stimulation of the secretion of various chemokines involved in the recruitment of immunocompetent cells at the subendothelial level, namely MCP-1, MIP-1ß, TNF-α, IL-1ß and IL-8, was also reported, mainly in the presence of 7ß-hydroxycholesterol and 25-hydroxycholesterol (54). Treatment of aortic rat smooth muscle cells with 25-hydroxycholesterol or 22R-hydroxycholesterol causes the accumulation of group IIA secretory phospholipase A(2) and increases enzyme activity (55).…”
Section: Oxysterols and Inflammatory Processesmentioning
confidence: 97%
“…Similarly, little information is available on oxysterolactivated metabolic pathways at the translational and posttranslational levels. However, in 7ß-hydroxycholesteroltreated U937 and THP-1 cells, it has been clearly established that IL-8 secretion is associated with activation of the MEK/ERK1/2 signaling pathway (54). Interestingly, in the presence of PD98059, a potent inhibitor of MEK, IL-8 secretion was totally counteracted, whereas no decrease in the IL-8 mRNA level or intracellular IL-8 was observed (54).…”
Section: Oxysterols and Inflammatory Processesmentioning
confidence: 99%
“…The same study demonstrated that IL-8 secretion was associated with activation of the ERK1/2 signaling pathway [31]. The oxysterols 7-K and 25-OH have also been observed to enhance IL-1 , IL-6, IL-8 and TNF-mRNA and secretion levels, in a dose-dependent manner, although to different extents.…”
mentioning
confidence: 80%
“…Further, in human monocytic cells, 7 -OH and 25-OH, but also to a lesser extent 7-K, are potent in vitro inducers of MCP-1, IL-8, IL-1 , tumor necrosis factor-(TNF-), macrophage inflammatory protein-1 (MIP-1 ), as well as of other inflammatory molecules [31]. The same study demonstrated that IL-8 secretion was associated with activation of the ERK1/2 signaling pathway [31].…”
mentioning
confidence: 99%